Sex-biased gene expression across mammalian organ development and evolution - Rodríguez-Montes, Leticia (Science, 2023)
Sexually dimorphic traits are common among mammals and are specified during development through the deployment of sex-specific genetic programs. Because little is known about these programs, we investigated them using a resource of gene expression profiles in males and females throughout the development of five organs in five mammals (human, mouse, rat, rabbit and opossum) and a bird (chicken). Sex-biased gene expression varies considerably across organs and species and is often cell type-specific. Sex differences increase abruptly around sexual maturity instead of increasing gradually during organ development. Finally, sex-biased gene expression evolves rapidly at the gene level, with differences between organs in the evolutionary mechanisms used, but slower at the cellular level, with the same cell types being sexually dimorphic across species.